FACTORS INFLUENCING CYBER-AGGRESSION: A SYSTEMATIC REVIEW - Moesarofah, Moesarofah (Jurnal Konseling Pendidikan Islam, 2025)
This systematic literature review aims to synthesize factors contributing to cyber aggression, drawn from various empirical studies. This review examines individual, social, and situational factors that shape the tendency of cyber aggression, as well as the interaction between factors. Referring to Grigg's theory, the dynamics of cyber aggression are influenced by various factors, ranging from the motivation of the perpetrator to the conditions of the social environment. Several relevant theories to explain such as Social Learning Theory, Cognitive Theory and Frustration-Aggression Theory. The research design uses a systematic literature review, from 2010-2024. Search through electronic databases: Frontiers, Elsevier, Springer, Routledge, and Google Scholar. Search keywords: "cyber aggression", and "factors that influence". After applying the inclusion criteria and removing several articles according to the research objectives, 19 articles were obtained to be identified and synthesized. The findings highlight the complex and multifactorial nature of cyber aggression, which underscores the need for a holistic approach to address this problem. This review provides a comprehensive overview of the existing literature, identifies gaps in knowledge, and offers implications for future research and practical applications.